Factores que limitan la exportación de artesanías al mercado extranjero desde la ciudad de Iquitos, año 2019 - Valdez Cardenas, Gino Valentin (2020)
The present study, sought to determine the factors that limit the export of handicrafts to the foreign market from the city of Iquitos, was handled under a descriptive-quantitative-cross-sectional investigation with a non-experimental design, in which 45 artisans from the city of Iquitos and to whom a survey was applied and was made up of 18 questions. After said survey, the study concluded that 54%, 56% and 67% of those surveyed consider that economic factors, commercial factors and factors related to transportation, respectively, greatly affected the export of handicrafts to the foreign market; as well as 54% of those surveyed consider that the performance of the product regularly affected the export of these crafts to the foreign market. Given this, the alternative hypothesis is accepted, that is, the economic, commercial factors, related to the product and transportation, significantly limit the export of handicrafts to the foreign market from the city of Iquitos, year 2019.